Batman returns [videorecording (DVD)] - Waters, Daniel; Keaton, Michael, 1951-; DeVito, Danny; Pfeiffer, Michelle, 1957-; Walken, Christopher, 1943-; Kane, Bob; Hamm, Sam; Elfman, Danny (Distributed by Warner Home Video, 2007)
Batman battles against the villains Catwoman and Penguin and crooked businessman-turned-mayoral candidate Max Schreck in Gotham City.